(untitled) (Bangladesh Journal of Physics, 2020)
Iron (Fe), a magnetic transition metal, doped manganese oxide (MnO2) nanostructured thin films were deposited onto glass substrates by a spray pyrolysis deposition technique at 450oC substrate temperature for glucose sensing performance. Fe concentration greatly affects the film surface morphology. The film was found to be more compact and porous for 4 at % Fe doping. The glucose response was measured by electrical four probe method using the pure MnO2 and 2, 4, 6, 8 at% Fe doped MnO2 thin films as an active electrode. It was determined that 4 at % Fe: MnO2 thin film with 20 nm crystallite size has high sensitivity, fast glucose response and recovery time. Optical band gap measurement indicated that the sensitivity increased as the band gap decreased up to 4 at % Fe concentration. The highest glucose sensing response was recorded about 29 % in 5 minutes. Bangladesh Journal of Physics, 27(1), 1-12, June 2020